2020
DOI: 10.1148/rycan.2020204013
|View full text |Cite
|
Sign up to set email alerts
|

Management of Lung Nodules and Lung Cancer Screening During the COVID-19 Pandemic: CHEST Expert Panel Report

Abstract: I n some parts of the world, the coronavirus disease 2019 (COVID-19) pandemic has stressed the health-care systems close to or even past their breaking point. Rightfully, much of the attention to date has focused on the immediate needs of patients suffering from the disease, particularly those who are critically ill. The strain on health-care systems and the need to control the virus using containment (testing and isolating cases) and mitigation (social distancing and shelter-in-place orders) have affected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 11 publications
4
56
0
1
Order By: Relevance
“…Nevertheless, there is a lack of studies examining the diagnosis of lung cancer and treatment guidelines during an epidemic. During the COVID-19 pandemic, several international societies presented guidelines for cancer diagnosis and treatments based on expert opinions [ 14 ]. However, these guidelines are not yet evidence-based.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a lack of studies examining the diagnosis of lung cancer and treatment guidelines during an epidemic. During the COVID-19 pandemic, several international societies presented guidelines for cancer diagnosis and treatments based on expert opinions [ 14 ]. However, these guidelines are not yet evidence-based.…”
Section: Discussionmentioning
confidence: 99%
“…The ACR provides guidance on safe resumption of routine care as we prepare to welcome patients back [8]. An expert panel also provides recommendations on management of lung nodules during the pandemic [9,10]. However, as much as we have guidance from professional societies, we have to convince patients to trust in our ability to protect them before elective service volumes will normalize.…”
Section: -Alexandre Dumasmentioning
confidence: 99%
“…Kumar S et al [9] suggested that in the case of limited surgical resources or high risks associated with perioperative care, NSCLC patients who presented with advanced yet localized disease that was resectable could be treated with speci c, non-surgical management, including chemotherapy, chemoimmunotherapy, radiation therapy, and immunotherapy. A previous consensus statement suggested that during the COVID-19 pandemic, the annual screening exam and treatment of clinical stage I NSCLC should be delayed [10] . The statement also concluded that it could be acceptable to delay the surveillance CT scan for approximately three to six months for patients with an incidentally detected pure GGN of any size, a partially solid lung nodule with a solid component of 6 to 8 mm, or a solid nodule that was less than 8 mm in diameter [10] .…”
Section: Introductionmentioning
confidence: 99%
“…A previous consensus statement suggested that during the COVID-19 pandemic, the annual screening exam and treatment of clinical stage I NSCLC should be delayed [10] . The statement also concluded that it could be acceptable to delay the surveillance CT scan for approximately three to six months for patients with an incidentally detected pure GGN of any size, a partially solid lung nodule with a solid component of 6 to 8 mm, or a solid nodule that was less than 8 mm in diameter [10] . Raskin J et al [11] recommended delaying surgery for up to three months in cases of small-size NSCLC that did not appear to grow rapidly, and the growth rate should be followed with chest CT scans.…”
Section: Introductionmentioning
confidence: 99%